Analysis of the relationship between particle number and fuel cutoff in a single-cylinder gasoline direct injection engine. (November 2020) - Song, Jingeun; Choi, Mingi
This study investigates the effects of fuel cutoff on particle number in a single-cylinder wall-guided gasoline direct injection engine. Various durations of fuel cutoff and change in load and engine stop were tested, and the in-cylinder pressure, particle number, and NO x emissions were measured. The change in in-cylinder temperature during combustion stop was calculated using the in-cylinder pressure and the ideal gas law. Experimental results showed that as the fuel cutoff duration increased, the particle number increased significantly when combustion resumed. For the injection timing before top dead center 330°, the particle number, which was 600 × 10 3  #/cm 3 under the continuous combustion condition, increased to 6700 × 10 3  #/cm 3 after 30 s of fuel cutoff. Both the fuel cutoff and engine stop showed enormous amount of particle number when combustion restarted. A major factor that increased particle number was the temperature reduction of piston during the combustion stop. The peak in-cylinder temperature decreased by 38 K during 30 s of motoring, which was induced by the temperature drop of the piston. Therefore, in terms of particulate emissions, it is more advantageous to lower the engine load than to stop combustion: the piston surface remains hot during load reduction. In addition, it is recommended to change the engine load slowly to reduce the particle number emissions. In this study, the rapid load change from indicated mean effective pressure of 0.25 to 0.55 MPa showed 7% higher particle number emissions than the gentle load change. On the contrary, NO x was reduced because none was generated during combustion stop. However, the fuel cutoff would increase NO x in gasoline vehicles because the oxygen in the unburned air would significantly reduce the conversion efficiency of a three-way catalytic converter. It is especially worth investigating the reason for the increase in emissions because it is easy to think that all kinds of emissions will be reduced if fuel is not burned.